The Timing of Intergenerational Transfers, Tax Policy, and Aggregate Savings - Altig, David; Davis, Steven J. (American Economic Review, 1992)
We analyze an overlapping-generations framework that accommodates two observations: (i) the interest rate on consumption loans exceeds the rate of return to savings, and (ii) private intergenerational transfers primarily occur early in the life cycle. Assuming altruistically motivated transfers in at least some family lines and other plausible conditions, we prove the invariance of capital's steady-state marginal product to government debt, government expenditures, and the tax rates on labor and capital income. We show that the tax treatment of household interest payments has powerful effects on capital intensity and aggregate savings in life-cycle and, especially, altruistic linkage models.